2014
DOI: 10.1002/jcla.21705
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Arkray/ELITech ADAMS HA‐8180V® with Bio‐Rad Variant,TMII Turbo2.0® and Tosoh Bioscience HLC®‐723G8 for HbA1c Determination

Abstract: The Arkray/ELITech ADAMS HA-8180V demonstrated high analytical performance similar to previous systems such as Biorad(TM) Variant II Turbo 2.0 and Tosoh Bioscience HLC-723G8. The three systems allow a high-quality HbA1c measurement and appeared interchangeable for diabetes diagnosis or for the therapeutic monitoring of patients without hemoglobin variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…During our study, we used an earlier software version 5.23 on TOSOH G8. Previous studies demonstrated reliable HbS, HbC, and HbD identification using TOSOH G8 in variant HbA1c mode . However, these studies focused only on effective detection of Hb variants and not on Hb variant quantification.…”
Section: Discussionmentioning
confidence: 99%
“…During our study, we used an earlier software version 5.23 on TOSOH G8. Previous studies demonstrated reliable HbS, HbC, and HbD identification using TOSOH G8 in variant HbA1c mode . However, these studies focused only on effective detection of Hb variants and not on Hb variant quantification.…”
Section: Discussionmentioning
confidence: 99%
“…HBB increases the risk of having T2D ( 39 ). HBD is detected in various systematic tests for diabetes ( 40 ). HBG2 is upregulated in diabetic retinopathy ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…So, in our HPLC method, Hb Hope and HbA1c elute in the same window leading to probable overestimation, like in other studies. 5,6 It is possible that alpha-thalassemia in patient-B justifies the lower overestimation of HbA1c in relation to patient-A in D-10 (Table 1).…”
Section: Letter To the Editormentioning
confidence: 99%